Altitude, temperature, and N Management effects on yield and yield components of contrasting lowland rice cultivars - Stuerz, S.; Chuma, B.A.; Cotter, M.; Kalisa, A.; Rajaona, A.; Senthilkumar, Kalimuthu; Vincent, I.; Asch, F. (Wiley, 2020)
Nitrogen (N) is one of the main nutrients that drive rice grain yield and is intensely managed especially in lowlands under irrigated conditions. A set of experiments was conducted in mid‐ and high‐altitude sites in Rwanda to investigate the response of five genotypes under different sowing dates and different N management. Genotype grain yields were higher and more stable at mid‐altitude across sowing dates. N rates strongly affected grain yield at mid‐altitude (p < .0001), but not at high altitude. Postponing basal N had positive effects on yield and yield components in both sites, with more pronounced effects at high altitude. Increasing N rate beyond 120 kg/ha led to a decrease in percentage of panicles per tiller and spikelet fertility and a decrease in grain yield due to excessive tillers at both high altitude and mid‐altitude. Thus, basal N application should be recommended at high altitude and the increase in N rate up to 120 kg/ha at mid‐altitude. A strict observation of recommended planting date should be followed at high altitude, and the use of cold‐tolerant genotypes is encouraged.